Trends in fabrication of polymers and polymer composites - Patel, Vinay Kumar; Kant, Rishi; Chauhan, Pankaj Singh; Bhattacharya, Shantanu 1974- (AIP Publishing, 2022)
"This book provides an in-depth review and discussion of the various fabrication technologies of polymers and polymer composites, including photochemical processes, laser-assisted methods, and additive manufacturing/3D printing. It covers the basic principles and protocols of polymer composite fabrication techniques, including synthesis, fabrication, characterization, and manufacturability. The book emphasizes the importance of nanofillers as reinforcements or additives, highlighting the nanotechnology trends in polymer fabrication.
Keywords: Polymers; Polymeric composites; Polymères; Composites polymères; polymers; TECHNOLOGY & ENGINEERING / Textiles & Polymers; TECHNOLOGY & ENGINEERING / Manufacturing; SCIENCE / Physics/Polymer